PENGARUH FOTOTERAPI TERHADAP PENURUNAN TANDA IKTERUS NEONATORUM PATOLOGIS DI RUMAH SAKIT GRANDMED LUBUK PAKAM - Dian Anggri Yanti; Iskandar Markus Sembiring; Syatriawati .; Junita Ika Susanti Br Ginting; Serliati Yusdi (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2021)
Pathological neonatal jaundice is a liver or liver disease which causes yellowing of the baby’s skin and newborn’s eyes. The yellow color that occurs is caused by hight bilirubin in the blood because that baby’s liver is not yet mature enough. Objective : this study generally aims to determine whether there is an effect of phototerapy on the reduction in pathological neonatal care unit (NICU) room at the Grandmed Lubuk Pakam Hospital in 2020. Method : The type of ths research is expermental quantitative with One Group pre Test and post-test,namely research using comparison ( control ) groups, measurements are carried out before and after treatment. Provision of phototerapy is beneficial iin reducing the pathological neonatal jaundice sign. The number of samples with male sex is 31 people ( 57.4%) and the sample of female gender is 23 people (42.6%). Results : The administration of phototeray for the reducton in pathological neonatal jaundice signs using statistical analysis paired t- test obtained a value of p 0,000 <c 0.05. Conclusion : There s significant effect on the administration of phototherapy on the decrease in pathological neonatal jaundice signs. Suggeston : The researcher recommends that the researcher recommends that the researcher recommends that the researcher recommends that the researcher further adds the number of samples and a longer time so that the results obtained are more optimal.